2020
DOI: 10.3390/cells9081758
|View full text |Cite
|
Sign up to set email alerts
|

The RNA Methyltransferase NSUN2 and Its Potential Roles in Cancer

Abstract: 5-methylcytosine is often associated as an epigenetic modifier in DNA. However, it is also found increasingly in a plethora of RNA species, predominantly transfer RNAs, but increasingly found in cytoplasmic and mitochondrial ribosomal RNAs, enhancer RNAs, and a number of long noncoding RNAs. Moreover, this modification can also be found in messenger RNAs and has led to an increasing appreciation that RNA methylation can functionally regulate gene expression and cellular activities. In mammalian cells, the addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(104 citation statements)
references
References 144 publications
(214 reference statements)
2
102
0
Order By: Relevance
“…DNMTs are involved in initiation of mammalian chromatin remodeling and gene expression regulation in diverse physiological and pathophysiological processes 23 , 24 . m5C functions as an important epigenetic modifier in DNA and RNA with transcriptional expression 25 . m5C plays vital roles in HNSCC carcinogenesis and tumor progression 22 .…”
Section: Discussionmentioning
confidence: 99%
“…DNMTs are involved in initiation of mammalian chromatin remodeling and gene expression regulation in diverse physiological and pathophysiological processes 23 , 24 . m5C functions as an important epigenetic modifier in DNA and RNA with transcriptional expression 25 . m5C plays vital roles in HNSCC carcinogenesis and tumor progression 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The m5C methyltransferase NSUN2 is over-expressed in multiple types of tumours such as breast and colorectal malignancies (Ref. 113 ). NSUN2 protein expression was found to be upregulated in 34% breast tumours through immunohistochemical analysis of tissue microarrays (Ref.…”
Section: Clinical Relevance Of Methylation In Cancersmentioning
confidence: 99%
“…RCMTs are known to play a wide variety of roles, notably ribosomal assembly, transcription regulation, mRNA nuclear export and tRNA cleavage and charging [ 55 ]. NSUN2 is known to be responsible for the majority of m 5 C in mRNA [ 56 , 57 ]. NSUN6 has been shown to be implicated in the formation of m 5 C in mRNA [ 58 ].…”
Section: Co- and Post-transcriptional Rna Modifications And Rna Modifying Proteinsmentioning
confidence: 99%
“…In eukaryotes, RNA m 5 C is catalyzed by RCMTs, including NOL1/NOP2/SUN domain (NSUN) family enzymes and DNMT2 ( Figure 2 B). NSUN2 is responsible for catalyzing the majority of m 5 C in mRNAs and non-coding RNAs [ 57 , 228 , 229 ]. Our study demonstrated a marked increase in NOP2/NSUN1 and NSUN2-mediated m 5 C in drug (5-azacitidine) resistant myeloid leukemia cells [ 127 ].…”
Section: Fine-tuning Chromatin and Transcription Through Rna Modifications And Rna-modifying Proteinsmentioning
confidence: 99%
See 1 more Smart Citation